Pt and CoB trilayer Josephson $$π $$ π junctions with perpendicular magnetic anisotropy - N. Satchell; T. Mitchell; P. M. Shepley; E. Darwin; B. J. Hickey; G. Burnell (Scientific Reports, 2021)
Abstract We report on the electrical transport properties of Nb based Josephson junctions with Pt/Co $$_{68}$$ 68 B $$_{32}$$ 32 /Pt ferromagnetic barriers. The barriers exhibit perpendicular magnetic anisotropy, which has the main advantage for potential applications over magnetisation in-plane systems of not affecting the Fraunhofer response of the junction. In addition, we report that there is no magnetic dead layer at the Pt/Co $$_{68}$$ 68 B $$_{32}$$ 32 interfaces, allowing us to study barriers with ultra-thin Co $$_{68}$$ 68 B $$_{32}$$ 32 . In the junctions, we observe that the magnitude of the critical current oscillates with increasing thickness of the Co $$_{68}$$ 68 B $$_{32}$$ 32 strong ferromagnetic alloy layer. The oscillations are attributed to the ground state phase difference across the junctions being modified from zero to $$π $$ π . The multiple oscillations in the thickness range $$0.2~\leqslant ~d_\text {CoB}~\leqslant ~1.4$$ 0.2 ⩽ d CoB ⩽ 1.4 nm suggests that we have access to the first zero- $$π $$ π and $$π $$ π -zero phase transitions. Our results fuel the development of low-temperature memory devices based on ferromagnetic Josephson junctions.